Third order nonlinear optical response exhibited by mono- and few-layers of WS2. (13th April 2016) - Torres-Torres, Carlos; Perea-López, Néstor; Elías, Ana Laura; Gutiérrez, Humberto R; Cullen, David A; Berkdemir, Ayse; López-Urías, Florentino; Terrones, Humberto; Terrones, Mauricio
Abstract: In this work, strong third order nonlinear optical properties exhibited by WS2 layers are presented. Optical Kerr effect was identified as the dominant physical mechanism responsible for these third order optical nonlinearities. An extraordinary nonlinear refractive index together with an important contribution of a saturated absorptive response was observed to depend on the atomic layer stacking. Comparative experiments performed in mono- and few-layer samples of WS2 revealed that this material is potentially capable of modulating nonlinear optical processes by selective near resonant induced birefringence. We envision applications for developing all-optical bidimensional nonlinear optical devices.